Prevalence of People with Down Syndrome in Brazil - Brandão, I. M.; Fonseca, V.; Madi, R. R. (Scientia Plena, 2012)
Down Syndrome (DS) is one of the most prevalent chromosomal changes, and therefore, deserves the study of chromosomal abnormalities. In Brazil there is no exact number for the quantity of people who have SD, only projections. Considering that better life and more efficient public policies aimed at those with SD directly depend on reliable data about its actual population, it is clear that there is a major deficiency in how they are surveyed and analyzed the information on the Brazilian population with SD.